Variations in Protein Concentration and Nitrogen Sources in Different Positions of Grain in Wheat - Li, Xiangnan; Zhou, Longjing; Liu, Fulai; Zhou, Qin; Cai, Jian; Wang, Xiao; Dai, Tingbo; Cao, Weixing; Jiang, Dong (Frontiers in Plant Science, 2016)
The distribution patterns of total protein and protein components in different layers of wheat grain were investigated using the pearling technique, and the sources of different protein components and pearling fractions were identified using 15N isotope tracing methods. It was found that N absorbed from jointing to anthesis (JA) and remobilized to the grain after anthesis was the principal source of grain N, especially in the outer layer. For albumin and globulin, the amount of N absorbed during different stages all showed a decreasing trend from the surface layer to the center part. Whereas, for globulin and glutenin, the N absorbed after anthesis accounted for the main part indicating that for storage protein, the utilization of N assimilated after anthesis is greater than that of the stored N assimilated before anthesis. It is concluded that manipulation of the N application rate during different growth stages could be an effective approach to modulate the distribution of protein fractions in pearled grains for specific end-uses.